2023
DOI: 10.1007/s40993-023-00463-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic reduction densities for elliptic curves

Francesco Campagna,
Peter Stevenhagen

Abstract: For an elliptic curve E defined over a number field K, the heuristic density of the set of primes of K for which E has cyclic reduction is given by an inclusion–exclusion sum $$\delta _{E/K}$$ δ E / K involving the degrees of the m-division fields $$K_m$$ K m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For the known bounds on c E , the reader may refer to Cojocaru [27] and Zywina [101]. When E has complex multiplication, the surjectivity is not true for large primes; see page 12 in [25]. In general, whether the elliptic curve E is without complex multiplication or not, Serre showed that for any m ∈ N with (m, 30) = 1, ρ E,m is surjective if and only if ρ E,ℓ is surjective for any prime ℓ | m.…”
Section: Galois Representations Of Composite Modulimentioning
confidence: 99%
“…For the known bounds on c E , the reader may refer to Cojocaru [27] and Zywina [101]. When E has complex multiplication, the surjectivity is not true for large primes; see page 12 in [25]. In general, whether the elliptic curve E is without complex multiplication or not, Serre showed that for any m ∈ N with (m, 30) = 1, ρ E,m is surjective if and only if ρ E,ℓ is surjective for any prime ℓ | m.…”
Section: Galois Representations Of Composite Modulimentioning
confidence: 99%